Management and Leadership in Community Gardens: Two Initiatives in Greater Christchurch, New Zealand - Sonja Burtscher (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2010)
In an increasingly urbanised world, significant land-use changes, environmental degradation, changes of society and lifestyles can be evidenced. Community gardens are examples for important, subsistent agricultural assets to a sustainable city development. They carry the potential to meet multiple needs of the dwellers such as community based natural resources management, local food supply, social (re)development, etc. This action research is particularly concerned with two different community gardens in the urban area of Greater Christchurch, New Zealand, in order to provide understanding of interrelations between leadership performance, management practice and social, environmental, cultural and economic 'effectiveness' of community gardens on a community level in urban environments. Findings argue that leadership and management affect interrelationships in multiple ways within a local community. A detailed investigation of different leadership concepts and management performances and group dynamics was undertaken that highlight the importance of a strategic organisation of these local initiatives. 'Effective' leadership that reacts according to the community garden community is essential for making community gardens relevant to its users, and with its implications on a wider social and physical urban environment.
Keywords: R; 330; Urban agriculture; Community garden; leadership; management; group dynamics; sustainable urban development; New Zealand